Modulus of elasticity of reinforced clay - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2011)
Reinforced soil has been among the most effective soil modification materials. Its use has been expanded rapidly into civil engineering, geotechnical engineering and pavement engineering. Reinforcing subgarde in pavement systems has always been an issue. This study focuses on effect of fibre inclusion on the modulus of elasticity of subgrade material. Plastic fibre was used for this investigation. Fibre contents and aspect ratio have been changed during these tests. The fibre percentage varied from 0 % (for unreinforced samples) to 3%. Clay was used as sub grade material. Unconfined compression tests were carried out to investigate behaviour of the composite under different condition. The fibre length and fibre content found to play important rule on the modulus of elasticity of fibre. Furthermore it was observed that ductility of sample increased by fibre inclusion. (2011) Trans Tech Publications, Switzerland.